Exploring strategies for sustainable ‘ecocampus’: the experience of Universiti Malaysia Sabah - Rosazman Hussin,; Velan Kunjuraman, (Faculty of Social Sciences and Humanities, UKM,Bangi, 2015)
The ideal of sustainability is to balance social needs with economic growth and environmental integrity. The importance of this ideal cannot be over-emphasised such that sustainable campus should be implemented in higher educational institutions to nurture the practice of environmental sustainability. In 2013, Universiti Malaysia Sabah (UMS) introduced the idea of sustainable campus (EcoCampus) accompanied by the establishment of EcoCampus Management Centre. This paper explores current strategies to achieve this vision of EcoCampus based on secondary sources of information. Reports regarding the UMS strategies to achieve sustainable campus were obtained for the period 2013 - February 2015. The findings reveal that UMS has successfully introduced a five-year plan for the period of 2013 to 2017 to transform UMS into EcoCampus including natural resource conservation and energy saving projects.